USE OF FLIPBOOKS IN LEARNING FIQIH TO IMPROVE CLASS 8 STUDENTS' UNDERSTANDING AT MTS MUHAMMADIYAH SUKARAME BANDAR LAMPUNG: A QUALITATIVE DESCRIPTIVE STUDY - Sriwijbant, Anjali; AD, Yahya; Wulandari, Heny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The digital era has brought a transformation in learning methods, introducing new tools and technologies that can increase student engagement and understanding. In this context, flipbooks emerge as one of the promising innovations in education, especially in fiqh learning at MTs Muhammadiyah Sukarame, Bandar Lampung. This research aims to describe the use of flipbooks as a learning medium and identify their impact on understanding fiqh material for grade 8 students. Using qualitative descriptive methods, this research explores student and teacher perspectives regarding the implementation of flipbooks in the learning process, through observation, in-depth interviews, and document analysis . It is hoped that the research results will provide insight into the effectiveness of flipbooks in facilitating a better understanding of Islamic jurisprudence concepts, offering more interactive and interesting learning alternatives, and increasing students' learning motivation. This research also aims to evaluate the challenges faced in implementing flipbooks and how these challenges can be overcome to maximize their potential as a learning tool. Thus, this study not only contributes to the literature on Islamic education and educational technology but also offers practical recommendations for the development of more effective and dynamic fiqh learning in the future.